Ny metode til at indsamle interviewdata om rejser med overnatning: Considerations on a method to analyse long distance travel when collecting only data about the two latest journeys - Christensen, Linda (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
The purpose of the paper is to present alternative methods to reduce the cost of long distance travel surveys in the hope that it should be more economically feasible to conduct such surveys regularly. A new Danish survey about journeys abroad with overnight stay(s) is used to investigate if it is possible to collect long distance travel data by only asking for information about the two latest journeys. It is shown that the time gap between the latest journey and the journey before this can be used to estimate a survival function for the probability to travel after a certain date. From this the annual number of journeys is calculated and a weight is extracted dependent on the time gap between two journeys. It is shown how these weights can be used as multipliers for calculating among others the annual travel distance, travel purpose and mode. The results are compared with a survey from 2010-11 Different kind of strengths and weaknesses compared to a traditional retrospective long distance travel survey are discussed, especially the memory effect. It is shown that the alternative methodology more than doubles the number of reported journeys compared to a retrospective survey reporting journeys during 3 months. Finally, the paper includes some recommendations on the questionnaire and the data collection process.